2013
DOI: 10.1136/annrheumdis-2012-202576
|View full text |Cite
|
Sign up to set email alerts
|

Janus kinase inhibitors in autoimmune diseases

Abstract: Biological therapies directed at proinflammatory cytokines have irrevocably changed the landscape of treatment of rheumatoid arthritis (RA) and other autoimmune diseases. With the advances in our knowledge in cytokine signaling, the question emerges whether targeting intracellular signaling might also be a safe and efficacious strategy. Janus kinases or Jaks are critical for a large family of cytokines and the first Jak inhibitor has been approved by the FDA for the treatment of myelofibrosis. Late phase clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
306
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 381 publications
(314 citation statements)
references
References 47 publications
3
306
1
4
Order By: Relevance
“…Proinflammatory cytokines implicated in the pathogenesis of rheumatoid arthritis (RA), including interleukin (IL) 6, IL-15, IL-17, IL-23, interferon-a/β, interferon-g, and granulocyte-macrophage colony stimulating factor 1,2 , primarily act through intracellular Janus kinase (JAK) signaling pathways 3 . Drugs that inhibit these pathways 3,4 , which may directly block cytokine signaling or indirectly modulate T cell functions through suppression of CD80/86 expression in dendritic cells 5 , are currently the focus of extensive development efforts for RA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Proinflammatory cytokines implicated in the pathogenesis of rheumatoid arthritis (RA), including interleukin (IL) 6, IL-15, IL-17, IL-23, interferon-a/β, interferon-g, and granulocyte-macrophage colony stimulating factor 1,2 , primarily act through intracellular Janus kinase (JAK) signaling pathways 3 . Drugs that inhibit these pathways 3,4 , which may directly block cytokine signaling or indirectly modulate T cell functions through suppression of CD80/86 expression in dendritic cells 5 , are currently the focus of extensive development efforts for RA.…”
mentioning
confidence: 99%
“…Drugs that inhibit these pathways 3,4 , which may directly block cytokine signaling or indirectly modulate T cell functions through suppression of CD80/86 expression in dendritic cells 5 , are currently the focus of extensive development efforts for RA. Baricitinib is a potent, selective, orally administered, reversible inhibitor of JAK signaling 6 .…”
mentioning
confidence: 99%
“…Several proinflammatory cytokines including interleukin 6 (IL-6), IL-12, IL-23, interferon, granulocytemacrophage colony-stimulating factor, and the γ chain cytokines including IL-2 use the Janus kinase (JAK) intracellular signaling pathway and have been associated with RA. Several small-molecule JAK inhibitors are in clinical development, each having a particular selectivity for inhibition of 1 or more of the 4 enzymes within the JAK family 1 .…”
mentioning
confidence: 99%
“…Due to this, and additional inhibition of the action of IFN, there is markedly increased the risk of cancer. 7 However, a meta-analysis showed that risk of infection with both JAK inhibitors and biological therapy is more or less the same. 16 Toafacitinib can additionally cause adverse effects like urinary tract infection, diarrhea, nasopharyngitis and upper respiratory infections.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Hence inhibiting these enzymes interrupts the signal transduction that results from the interaction of cytokines with their receptors. 6,7 …”
Section: Introductionmentioning
confidence: 99%